Comparative Study of Zn Loading on Advanced Functional Zeolite NaY from Bagasse Ash and Rice Husk Ash for Sustainable CO2 Adsorption with ANOVA and Factorial Design - Patchaya Tobarameekul; Supawon Sangsuradet; Patcharin Worathanakul (Atmosphere, 2022)
The objectives of the research were to develop synthesis and estimation of each factor on carbon dioxide adsorption of advanced functional zeolite NaY material derived from bagasse ash and rice husk ash with different crystallization temperatures and weight percentages of zinc by the ion exchange method. The adsorbents were tested in a packed bed reactor at different temperatures and flow rates of carbon dioxide. The Minitab program was used to estimate the effects of each factor on carbon dioxide adsorption properties. The results showed that extracted silicon dioxide from bagasse ash and rice husk ash could be successfully used as raw material for zeolite NaY synthesis with a crystallization temperature of 298.15 K. The zeolite NaY crystalline structure was well-preserved after ion exchange. The highest capacity of carbon dioxide adsorption was at 10.33 mmol/g with zeolite 5B298-373-1. The results of the Minitab program showed that the carbon dioxide adsorption decreased with increasing crystallization temperature and carbon dioxide flow rate parameters. However, the increased weight percentage of zinc loading on zeolite NaY resulted in better carbon dioxide adsorption. The factors of the types of adsorbents and adsorption temperature showed interaction with each other.